West Bank and Gaza : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2022)
For more than a decade, commercial banks in West Bank and Gaza (WBG) have struggled to manage buildups of excess physical Israeli shekel cash. Banks elsewhere typically manage the amount and currency composition of physical cash they hold in their vaults through transactions with other commercial banks and central banks. However, citing money laundering and terrorism financing (ML/TF) concerns, the two Israeli banks that currently offer correspondent services to banks operating in WBG no longer offer them cash services. The Bank of Israel (BoI) has imposed limits on the amount of shekel coins and notes it accepts back from Palestinian banks. This has long hindered liquidity management and been a drag on the profitability of Palestinian banks, but periodic large increases in excess cash in recent years have created additional risks and raised the costs to the Palestinian banking system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; International Agreements and Observance; International Organizations; Monetary Policy